Evaluasi Ketersediaan Ruang Terbuka Hijau dan Penerapan Konsep Kota Hijau di Provinsi DKI Jakarta - Nurfadhil, Reza; Zain, Alinda Fitriany Malik (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2024)
DKI Jakarta Province with a high increase in development activities has implications for the conversion of urban Green Open Space (GOS) into built-up land. The importance of urban GOS can not be separated from supporting the development of the green city. The green city is a concept of realizing a sustainable city and minimizing urban landscape degradation. This research aims to evaluate the availability of urban GOS and the implementation of the green city concept in DKI Jakarta. Geographic Information System (GIS) based spatial analysis methods and remote sensing were used to evaluate the availability of urban GOS. Quantitative and qualitative analysis methods based on the Asian Green City Index (AGCI) are used to evaluate the implementation of the green city concept. The results show that GOS in DKI Jakarta has decreased, from 33.70% in 2000, 23.47% in 2010, and 19.50% in 2020. In the implementation of the green city concept, the performance of DKI Jakarta has increased. Performance in 2000 was at a below-average level (34.58%), in 2010 it was at the average level (44.85%), and in 2020 the performance increased to an above-average level (62.76%). The results showed that the increase in the implementation of the green city concept has not been followed by an increase in the quantity of urban GOS. An integrative urban planning strategy is needed in developing DKI Jakarta and oriented towards the carrying capacity of the landscape and maintaining the availability of urban GOS.